Liuwei Dihuang pill cures postmenopausal osteoporosis with kidney-Yin deficiency: Potential therapeutic targets identified based on gene expression profiling. Issue 31 (August 2018) - Xu, Feng; Gao, Feng
Abstract : Abstract: This study aimed to investigate the potential therapeutic targets of Liuwei Dihuang pill (LDP) in the treatment of postmenopausal osteoporosis with kidney-Yin deficiency (PMO-KY). Gene expression data were downloaded from the GEO database, including 4 PMO-KY samples and 3 healthy postmenopausal controls from GSE56116, as well as 3 PMO-KY samples before LDP treatment and 3 PMO-KY samples after three months of LDP treatment from GSE57273. Limma package was used to identify differentially expressed genes (DEGs). Afterwards, the potential target genes of LDP (namely key DEGs) were identified according to the comparison of DEGs in PMO-KY group and the DEGs in LDP treatment groups. Subsequently, iRegulon plugin in Cytoscape software was used to predict potential transcription factors (TFs) that regulated the key DEGs, and Comparative Toxicogenomics Database was utilized to identify known PMO-related genes among the key DEGs. Totally, 202 and 2066 DEGs were identified between PMO-KY and controls, as well as after-treatment and before-treatment groups, respectively. Among them, 52 DEGs were up-regulated in PMO-KY but down-regulated after LDP treatment, and 8 TFs were predicted to these DEGs. Furthermore, 34 DEGs were down-regulated in PMO-KY but up-regulated after treatment, and 7 TFs were predicted to regulate these DEGs. Additionally, 43 of the 86 key DEGs were known PMO-related genes. NCOA3, TCF4, DUSP6, PELI2, and STX7 were predicted to be regulated by HOXA13 . In the PMO-KY treatment, NCOA3, TCF4, DUSP6, PELI2, and STX7 might be the potential therapeutic targets of LDP. However, further investigation is required to confirm these genes. Abstract : Supplemental Digital Content is available in the text